PEMANFAATAN TANAMAN OBAT OLEH SUKU JERIENG DI KABUPATEN BANGKA BARAT - Novalia Novalia; Budi Afriyansyah; Lina Juairiah (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2018)
Indonesia has been know as own high diversity of flora and fauna. In addition, Indonesia has been know high diversity of ethnics which has various distinctive traditions, including local knowledge. One of the local knowledge on using of traditional medicinal plants. The utilization of plants as medicinal plants has never been reported yet because of the changes of era, the local wisdom knowledge especially for medicinal plants has faded away. The purpose of this research is to determine the local knowledge of Jerieng ethnic in utilizing the plant include the parts of the plant, the processing, and the benefit as medicinal plants), collecting data of the medicinal plants diversity (species numbers, scientific name, local name, familes, habitat and habitus). The method of this research was used the qualitative and descriptive analysis. Data was collected from survey and interview in the Jerieng ethnic using snowball sampling. The result of research show there are 82 plants species 52 families, 16 informans, and 45 species disease. The most dominant families of medicinal plants is Zingiberaceae with 7 kinds and graminae//poaceae with 6 kinds. The most frequent used part of the plants by Jerieng ethnic are the leaf 46%, trunk habitus species 35% and the higher habitat is at plants garden house 52%. Meanwhile for the most used processing is by boiling the medicinal plants.